Pemberdayaan Masyarakat melalui Proyek Gaduhan Sapi Potong di Kecamatan Oba Tengah dan Oba Utara, Tidore Kepulauan, Maluku Utara (Project of Cattle Sharing System as a Means for Community Development in Oba Tengah and Oba Utara Subdistricts, Tidore Kepula - Supriyanti Djaelani; Rini Widiati; Krishna Agung Santosa (Faculty of Animal Science, Universitas Gadjah Mada, 2009)
To financially evaluate the Project of Cattle Sharing System in Oba Tengah and Oba Utara subdistricts, Tidore Kepulauan, Maluku Utara, a survey was conducted on 30 respondents purposively sampled using questionnaires. Data were analyzed using the criteria of benefit/cost ratio (BCR), net present value (NPV), internal rate of return (IRR) and net farm income of individual farmers whether or not participating the project. Using interest rate of 12% within four years when the farmers do not participate the project, resulted in the NPV of Rp. 17,185,232; when the farmers participate the project resulted in the NPV of Rp. 25,492,426, meaning there was an income increase of 67.41% and the increase of employment was found to be 5.34%. Average income share per year coming from project of cattle sharing system was Rp. 3,611,250 aside from family labor income, family investment income and family management income. It is concluded that the project of cattle sharing system is an effective means of community empowerment in terms of income, employment and the increase of cattle population.(Key words: Empowerment, Cattle sharing system, Income)